2023
DOI: 10.1002/jcb.30407
|View full text |Cite
|
Sign up to set email alerts
|

New insights on the catalytic center of proteins from peptidylprolyl isomerase group based on the FOD‐M model

Abstract: Generating the structure of the hydrophobic core is based on the orientation of hydrophobic residues towards the central part of the protein molecule with the simultaneous exposure of polar residues. Such a course of the protein folding process takes place with the active participation of the polar water environment. While the self‐assembly process leading to the formation of micelles concerns freely moving bi‐polar molecules, bipolar amino acids in polypeptide chain have limited mobility due to the covalent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…The elimination of a few residues produces significant differences in the level of O i toward T i and helps identify that part of the protein where the hydrophobicity pattern is micelle-like. These eliminated residues (with a local deficit in hydrophobicity due to the frequently present cavity) are generally residues that constitute the active center . The local superficial excess of hydrophobicity is often used for the complexation of another chain with a similar hydrophobicity exposure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The elimination of a few residues produces significant differences in the level of O i toward T i and helps identify that part of the protein where the hydrophobicity pattern is micelle-like. These eliminated residues (with a local deficit in hydrophobicity due to the frequently present cavity) are generally residues that constitute the active center . The local superficial excess of hydrophobicity is often used for the complexation of another chain with a similar hydrophobicity exposure .…”
Section: Resultsmentioning
confidence: 99%
“…These eliminated residues (with a local deficit in hydrophobicity due to the frequently present cavity) are generally residues that constitute the active center. 39 The local superficial excess of hydrophobicity is often used for the complexation of another chain with a similar hydrophobicity exposure. 23 The amphipathic membrane environment requires a hydrophobicity ordering that opposes the micelle-like ordering.…”
Section: Resultsmentioning
confidence: 99%
“…Treating all mentioned methods together with the model proposed in this paper may deliver an effective tool for the de novo design of enzymes of expected, defined activity. 86 …”
Section: Discussionmentioning
confidence: 99%
“…Next, the reaction solution with H 2 O 18 was applied to determine the oxygen source of photo-oxidation. 46 Interestingly, the monooxidation product was still dominated with 16 O (from dissolved O 2 ), while both 16 O and 18 O were incorporated into the multipleoxidation forms of products (Fig. S11B †).…”
Section: The Mechanism Of Photochemical Triuoromethylationmentioning
confidence: 99%
“…Hydrophobic interaction is essential during protein folding into an ordered structure with a hydrophilic surface and hydrophobic core. 11,12 Further, the protein recognition of small molecules such as drugs, 13,14 ligand binding with receptors, 15 and enzyme biocatalysis reactions 16,17 oen occur in protein hydrophobic pockets with essential functional hotspots. Recently, studies of structural biology have reported the key binding sites in the hydrophobic pockets of membrane proteins, such as vitamin K epoxide reductases (VKOR) with vitamin K antagonists, 18 ATP-binding cassette (ABD) transporters with inhibitors, 19 and G-protein-coupled receptors (GPCRs) with various ligands.…”
Section: Introductionmentioning
confidence: 99%